Sustainable Manufacturing Challenges, Solutions and Implementation Perspectives - Stark, Rainer; Seliger, Günther; Bonvoisin, Jérémy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Sustainability imposes an unprecedented challenge on society and has become the driving force of an urgent search for innovative solutions in all branches of economy. Manufacturing plays a key role in many areas of human living, and it is both part of the problem and of the solution. This book offers an overview of the broad field of research on sustainability in manufacturing with a particular focus on manufacturing technology and management. It summarizes the current challenges, describes best in class methods for development of sustainable manufacturing solutions and offers implementation perspectives. This volume covers areas of research such as production processes, product development, business model and corporate development, macro economy and education. The target audience primarily comprises research experts and practitioners in the field of manufacturing, but the book may also be beneficial for graduate students. .
Challenges -- Solutions -- Implementation perspectives -- Glossary. .
Keywords: Manufactures; Sustainability; Energy policy; Energy and state; Production management; Machines, Tools, Processes; Sustainability; Energy Policy, Economics and Management; Production